Celastrol ameliorates osteoarthritis via regulating TLR2/NF-κB signaling pathway - Yang, Guangxia; Wang, Kai; Song, Hua; Zhu, Rujie; Ding, Shuai; Yang, Hui; Sun, Jian; Wen, Xin; Sun, Lingyun (Frontiers in Pharmacology, 2022)
Objectives: Osteoarthritis (OA) is a joint disease characterized by degeneration of joint cartilage and is a significant cause of severe joint pain, physical disability, and impaired quality of life in the aging population. Celastrol, a Chinese herbal medicine, has attracted wide interests because of its anti-inflammatory effects on a variety of diseases. This study aimed to investigate the effect of celastrol on OA as well as the mechanisms in vivo and in vitro. Methods: A rat knee OA model was established using “medial collateral ligament transection (MCLT) + partial meniscectomy (pMMT)”. Eight weeks after surgery, the OA rats started to receive intra-articular injection of celastrol (1 mg/kg) once a week. Safranin O-fast green (S&F) and hematoxylin and eosin (H&E) staining were used to estimate histopathological changes. Micro-CT was used to evaluate bone volume of the subchondral bone of the knee joint. Chondrocytes were isolated from the knee cartilage of rats and OA patients. Enzyme linked immunosorbent assay (ELISA), Western Blot (WB), Polymerase Chain Reaction (PCR), and Immunohistochemistry (IHC) were used to detect the expression of inflammatory factors and stromal proteins, respectively. Results: We found that celastrol treatment significantly delayed the progression of cartilage damage with a significant reduction in osteophyte formation and bone resorption in OA rat model. In IL-1β-stimulated rat chondrocytes, celastrol significantly suppressed the production of inflammatory factors such as cyclooxygenase-2 (COX2), interleukin-6 (IL-6), and prostaglandin E2 (PEG2), and reduced IL-1β-induced matrix degradation by down-regulating the expression of matrix metalloproteinase 13 (MMP13). In addition, we found that toll-like receptor 2 (TLR2) was up-regulated in OA patients and rat knee OA models, while celastrol inhibited TLR2 signal and its downstream nuclear factor-kappa B (NF-κB) phosphorylation. Conclusion: In summary, celastrol may improve OA by inhibiting the TLR2/NF-κB signaling pathway, which provides innovative strategies for the treatment of OA.